Detection of the PR5 Gene Associated with Downy Mildew Resistance and Genetic Diversity Analysis of S2 Lines of Local Maize (Zea mays L.) From South Sulawesi Using SSR Markers - Rahma, Sitti; Juhriah; Agus, Rosana (HAYATI Journal of Biosciences, 2026)
A significant decline in corn production is often associated with downy mildew (Peronosclerospora maydis), while maize varieties with genetic resistance to this disease are still relatively limited. A molecular-based approach is needed, such as Phatogenesis Related (PR5) gene detection, to identify maize genotypes that are potentially resistant to downy mildew. This study aims to identify the presence of the PR5 gene and analyze genetic diversity in local maize from South Sulawesi, Srikandi kuning (national variety), and Carotenoid sync 3 from International Maize and Wheat Improvement Center (CIMMYT) to support the acceleration of downy mildew-resistant plant breeding programs. PR5 gene detection was carried out by extracting RNA according to the Total RNA Mini Kit Plant (Geneaid) procedure followed by PCR techniques with specific primers. Genetic diversity analysis was carried out using 15 polymorphic SSR primers. DNA amplification showed that 23 individuals were detected as containing the PR-5 gene from 30 samples tested based on the results of agarose gel electrophoresis. The PIC value obtained from the Simple Sequence Repeats (SSR) primers showed a high level of genetic diversity ranging from 0.64 to 0.93 with an average of 0.85. The genetic similarity matrix was calculated and analyzed using the UPGMA method using NTSYS version 2.2, producing a dendrogram with two main clusters. Cluster I has only one individual with a large genetic distance, while Cluster II is divided into two subclusters, IIA and IIB, reflecting the genetic closeness of most individuals. Individuals with PR5 genes and high genetic diversity were identified as potential candidates for use in a superior maize breeding program resistant to downy mildew disease.